PENCIPTAAN MOTIF BATIK SIDOARJO DENGAN SUMBER IDE KUPANG LONTONG - Fianty, Nesty Ayu; Arifiana, Deny (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
Kupang lontong is a traditional dish from Sidoarjo, consisting of mussels (kupang), rice cakes (lontong), lentho (fried mung bean fritters), shrimp paste (petis), raw garlic, and a flavorful broth that is tangy, spicy, and sweet. The dish is closely tied to coastal culture and the mussel-fishing community. This research aims to create Sidoarjo batik motifs by using kupang lontong as visual inspiration. Sidoarjo often incorporates ethnic foods into its batik designs, such as Jetis batik, which features motifs of rice and spinach flowers (kembang bayem), as spinach commonly grows in the region. This practice to transform kupang lontong into a batik design. The method follows theory of creation, which includes exploration, design, realization, and presentation. Ten designs were developed, three of which were realized as batik using the hand-drawn technique on primisima fabric measuring 115 × 200 cm. Naphthol as Synthetic dyes were used to produce vibrant colors. The result Sidoarjo batik motifs depict visual elements of kupang lontong, fishermen, and coastal scenery, combined with signature spinach flower (isen-isen kembang bayem) patterns typical of Sidoarjo batik. creation seeks to offer fresh ideas for developing batik motifs rooted in local richness.